Elephant Speak : A Devoted Keeper's Life Among the Herd. - Crandall, Melissa (Ooligan Press, 2020)
Through the story of one man's extraordinary bonds with the elephants he cares for, Elephant Speak: A Devoted Keeper's Life Among the Herd shows that progress is possible when we accept our shortcomings and embrace conversation.